ChemInform Abstract: Nickel‐Catalyzed Allylic Alkylation with Diarylmethane Pronucleophiles: Reaction Development and Mechanistic Insights. Issue 21 (6th May 2016) - Sha, Sheng‐Chun; Jiang, Hui; Mao, Jianyou; Bellomo, Ana; Jeong, Soo A.; Walsh, Patrick J.
Abstract: Selective mono‐ and di‐allylation reactions of diarylmethanes (I) and (VI), fluorene (XIII), and xanthene (XVI) are reported.